A development of the instructional process based on strategies-based instruction, learning cycle model and interactional feedback to enhance paragraph writing ability of undergraduate English majors - Ra-Shane Meesri (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2008